PENGARUH BOPO TERHADAP PROFITABILITAS BANK PERKREDITAN RAKYAT MALIFUT DANATAMA TERNATE - Mahmud, Muhammad Daud bin; Balamo, Wahyuni (Institut Agama Islam Negeri (IAIN) Ternate, 2021)
This study aimed to determine the effect of Operational Expenses on Operating Income (BOPO) on the Profitability of the Rural Bank (BPR) Malifut Danatama Ternate. Profitability in this study was measured using the ratio of Net Profit Margin (NPM). The alternative hypothesis proposed in this study is that BOPO has a negative and significant effect on the profitability of PT. BPR Malifut Danatama Ternate. The data in this study used secondary data, namely the financial statements of BPR Malifut Danatama for the period 2010 - 2020. The data were analyzed using simple regression, using SPSS 26. The results of this study accepted the proposed hypothesis, meaning that BOPO had a negative and significant effect on the profitability of PT. BPR Malifut Danatama Ternate. The effect of BOPO on Profitability means that every increase in BOPO will decrease the NPM value.